Studi Kesesuaian Lahan Budidaya Rumput Laut Berdasarkan Parameter Biofisik Perairan di Yensawai Distrik Batanta Utara Kabupaten Raja Ampat - Dirk Runtuboi; Yunus P. Paulungan; Tri Gunaedi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2014)
One of the potential areas for developing mariculture in Raja Ampat Regency is Yensawai. This research aim to determine biophysical parameter for seaweed culture. The parameters were proped in to four classes; high suitable, suitble, currently not suitable and permanently not suitable. The result showed that the cultivation area size were 14 hectares, where Ramon 1 and Ramon 2 Stations were categorized as currently not suitable, while Warkabas and Metabai stations were grouped into suitable for seawed cultivation.Key words: analysis of suitability, seaweed cultivation, Yensawai